Evaluasi higroskopisitas dan sifat alir serbuk serta granul parasetamol menggunakan metode corong, sudut istirahat, dan uji kelembaban - Chotimah, Wahyu Ningtyas Chusnul (Maliki Interdisciplinary Journal, 2026)
Paracetamol is an active pharmaceutical ingredient widely used in solid dosage forms, but it has limitations in the form of poor flow properties and sensitivity to humidity. The hygroscopicity and flow properties of paracetamol powder or granules are important parameters that need to be evaluated because they affect physical stability, the production process, and the quality of the final preparation. This study aims to evaluate the hygroscopicity and flow properties of paracetamol powder/granules through funnel method testing, angle of repose method, and humidity test. Flow properties are determined by measuring the flow time using the funnel method and the angle of repose value formed from the pile of powder or granules. Hygroscopicity is evaluated through humidity test by observing the change in sample weight after storage at certain humidity conditions. The test results show that paracetamol powder has poor flow properties, characterized by a longer flow time and a larger angle of repose value compared to paracetamol granules. Paracetamol granules show improved flow properties due to the formation of larger and more uniform particles, thereby reducing interparticle cohesion. Moisture testing showed that both paracetamol powder and granules were hygroscopic, but the moisture absorption rate of the granules was lower than that of the powder. This indicates that the granulation process can improve the physical stability of paracetamol against the effects of humidity. Based on the research results, it can be concluded that granulation has a positive effect on reducing hygroscopicity and improving the flow properties of paracetamol, making it more suitable for use in the manufacturing process of solid dosage forms such as tablets.